Distributed Energy Resources Scheduling with Demand Response Complex Contract - Faria, Pedro (2021)
Demand response is a very flexible way to improve distributed energy resources scheduling. The innovative contribution of this paper is to include in the model complex contracts approach, which can accommodate constraints according to the particular expectations of each player. Such contracts are included in the distributed energy resources scheduling optimization to dispatch demand response according to the consumers expectations. Multiperiod demand response events are considered. In this way, consumers can specify limits on the time, power, and remuneration regarding participation in demand response events, in a way that has not been considered in the literature. The state of the art treats these aspects separately or using a statistic approach, without providing consumers with options to combine their preferences regarding different aspects of their flexibility deployment. The model has been validated for 218 consumers using several scenarios and different types of distributed generation, showing that it is possible to increase demand response respecting consumers preferences.